1996
DOI: 10.1007/s00585-996-1413-8
|View full text |Cite
|
Sign up to set email alerts
|

EISCAT verification in the development of ionospheric tomography

Abstract: Abstract. This paper highlights the important role played by the EISCAT radar for verification in the development of tomographic techniques to produce images of ionospheric electron density. A brief review is given of some of the stages in the application of tomographic reconstruction techniques to the ionosphere. Results are presented to illustrate the effectiveness of the method in imaging ionospheric structures at high latitudes. In addition, the results include the first tomographic image of the ionosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The European Incoherent Scatter radar facility (EISCAT) has played a crucial role in the development of ionospheric tomography, in providing independent veri®cation of tomographic images. An overview of this important role is given by Walker et al (1996). Comparisons of tomographic reconstructions of ionospheric plasma distribution and EISCAT observations have been used to investigate several aspects of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…The European Incoherent Scatter radar facility (EISCAT) has played a crucial role in the development of ionospheric tomography, in providing independent veri®cation of tomographic images. An overview of this important role is given by Walker et al (1996). Comparisons of tomographic reconstructions of ionospheric plasma distribution and EISCAT observations have been used to investigate several aspects of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…The technique became popular after Austen et al (1988) demonstrated the feasibility to image ionospheric electron density distributions. Two-dimensional ionospheric profile sections varying in latitude and height were initially reconstructed using Navy Navigation Satellite System observations (Andreeva et al 1990;Fougere 1995;Walker et al 1996;Sutton and Na 1996;Kunitsyn et al 1997). In recent years, many researchers have been involved investigating GPS-based CIT (Ruffini et al 1999;Mitchell and Spencer 2003;Ma and Maruyama 2005;Stolle et al 2006;Jin et al 2006;Wen et al 2007a, b, c).…”
Section: Introductionmentioning
confidence: 98%
“…Radio tomography was introduced by Austen et al [1988] and has since been successfully used for the characterization of ionospheric structure [ Fougere , 1995; Walker et al , 1996; Sutton and Na , 1996; Kamalabadi et al , 1999] by integrated line‐of‐sight measurements. Radio tomography has recently been shown to be a promising new technique for large‐scale remote sensing of Earth's magnetosphere in theoretical studies with magnetohydrodynamic (MHD) simulations [ Ergun et al , 2000; Ganguly et al , 2000; Zhai and Cummer , 2005], as well as in satellite radio propagation experiments [ Cummer et al , 2001; Cummer et al , 2003].…”
Section: Introductionmentioning
confidence: 99%